2019
DOI: 10.1186/s12957-019-1608-6
|View full text |Cite
|
Sign up to set email alerts
|

Malignant ureteral obstruction: experience and comparative analysis of metallic versus ordinary polymer ureteral stents

Abstract: Background To study the outcome and experience of using metallic stents in treating patients with malignant ureteral obstruction (MUO). Methods Seventy-six patients with MUO were assigned to the metallic stent group (MSG) or the ordinary polymer stent group (OPSG) according to the different materials. The success rate of the operation, duration of operation, patency rate serum creatinine values ,postoperative complications and QOL scores were compared between the two gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 25 publications
0
31
0
Order By: Relevance
“…Previous studies by Abbasi et al and Chow et al showed a mean duration of functioning metallic stent of 5.3 to 7.4 months 11‐14 . Others reported the one year patency rates of Resonance metallic stents in malignancy ureteric obstruction ranged from 60% to 91% 15‐18 …”
Section: Discussionmentioning
confidence: 96%
“…Previous studies by Abbasi et al and Chow et al showed a mean duration of functioning metallic stent of 5.3 to 7.4 months 11‐14 . Others reported the one year patency rates of Resonance metallic stents in malignancy ureteric obstruction ranged from 60% to 91% 15‐18 …”
Section: Discussionmentioning
confidence: 96%
“…These stents have historically consisted of a polymer tube with multiple fenestrations to allow drainage, but metallic ureteral stents have also been designed in numerous configurations. [4,5]. For these metallic stents, a metal coil may be embedded within the polymer; more recent designs are configured in a metallic spiral design.…”
Section: Uretermentioning
confidence: 99%
“…Extraluminal ureteral compression can also occur from masses or lymphadenomegaly. Lastly, after radiation therapy in the region of the ureter, ureteral obstruction can result from fibrosis-induced stricture or alteration of ureteral elasticity with subsequent decreased peristaltic activity [4,5,21].…”
Section: Uretermentioning
confidence: 99%
“…A malignant ureteral obstruction develops secondary to a malignant tumor. A primary tumor may infiltrate the ureteral wall and compress the ureter, swollen lymph nodes may wrap around the ureter, edema and retroperitoneal fibrosis that develop after radiotherapy may distort the ureter or cause luminal stenosis, or ureter elasticity may be weakened [ 8 ]. The condition may be unilateral or bilateral.…”
Section: Upper Urinary Tract Obstructionmentioning
confidence: 99%